PENGARUH PEMBELAJARAN PROBLEM SOLVING TERHADAP KETERAMPILAN PEMECAHAN MASALAH SISWA SMP - Muhammad Muslim; Rahmat Yunus; Arif Sholahuddin (Universitas Lambung Mangkurat, 2022)
Learning generally still takes place traditionally with teacher-centered characteristics, using an expository approach so that the teacher dominates the process of learning activities in the class-room while the students are passive. Problem solving learning model is expected to be able to solve these problems. The research method uses a quasi-experimental model (quasi-experimental) with a